A conceptual framework for measuring e-banking service quality and customer satisfaction: Integrating SERVQUAL and TAM in the context of Nepal - Shrestha, Laba Kumar; Paudel, Ram; Paudel, Rajesh (Journal of Islamic Economic Insights, 2025)
This conceptual paper develops a comprehensive framework for analyzing service quality and customer satisfaction in Nepal’s e-banking industry by modifying the SERVQUAL model with the Technology Acceptance Model (TAM). Despite the spread of e-banking adoption, especially in urban areas, the quality of digital services is still uneven, which can be explained by the lack of infrastructure, digital literacy, and existing security issues. The suggested framework integrates five fundamental SERVQUAL dimensions–reliability, responsiveness, assurance, tangibles, and empathy–with TAM constructs, such as trust, perceived usefulness, and perceived ease of use. Trust was set as a mediating variable, and access to digital infrastructure was appointed as a contextual moderator. The purpose of this study is to provide a formal foundation for further empirical verification using structural equation modeling. The proposed framework provides a theoretical approach to improving digital banking strategy and creating user trust, and thus can enhance inclusive financial participation in developing economies such as Nepal.